Managerial Incentives and Market Integration - Jörgen W. Weibull (The Research Institute of Industrial Economics (IUI), 1996)
This paper develops a new analytical approach to the old question whether market conditions may influence the internal efficiency of firms. The basic textbook model of the firm is slightly extended to incorporate managers' incentives to reduce production costs in an imperfectly competitive product market. This is done without invoking any agency problem or other form of information asymmetry in firms. The analysis extends Marshallian and Hicksian consumer analysis to managers' demand for leisure in imperfectly competitive environments with a fixed number of firms, and free entry, respectively. Conditions are identified under which product market integration enhances the internal efficiency of firms, and it is shown that market integration is Pareto improving under free entry.
Keywords: A00; 330